PERSONALITY TRAITS OF BABY IN BABY DRIVER MOVIE - Prasetyo Prasetyo; Meisuri Meisuri; Juli Rachmadani Hasibuan (State University of Medan, 2020)
This study aimed at analyzing the kind of traits which represented by Baby in Baby Driver movie by Edgar Wright. The study of Characterization has been thrived in recent centuries. Personality Traits study in a movie is an interesting way to develop and identify some character in movies. The study used descriptive qualitative method. The data of this study were dialogues and statements from Baby which related to the Personality Traits theory in the movie script. The source of the data was Baby Driver movie. The findings of the Big Five theory analyzed by described the utterances and statements from Perlocutionary Act findings. It was found that there were five traits represented by Baby along the movie. They were (1) Introvert/Extrovert, (2) Neuroticism, (3) Conscientiousness, (4) Openness to Experience, and (5) Agreeableness. This study also proved that conflicts always happened in human being, especially teenager. At one time, a person chose to be introvert and in the next day he or she chose to be extrovert. Characterization learning was believed as a tool to differ one character of a movie or real-life individual from another.Keywords: Personality Traits, Speech Act, Perlocutionary Act.